Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 7 - Functions and Graphs - 7.4 The Algebra of Functions - 7.4 Exercise Set: 24

Answer

$-1$

Work Step by Step

RECALL: $(F-G)(x) = F(x) - G(x)$ Using the formula above gives: $(F-G)(x) \\= F(x)-G(x) \\=(x^2-2)-(5-x) \\=x^2-2-5-(-x) \\=x^2-7+x \\=x^2+x-7$ To find $(F-G)(2)$, substitute $2$ to $x$ in the equation above to obtain: $(F-G)(x) = x^2+x-7 \\(F-G)(2) = 2^2+2-7 \\(F-G)(2)=4+2-7 \\(F-G)(2)=6-7 \\(F-G)(2)=-1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.